SINTESIS DAN KARAKTERISASI MAGNETIT (Fe3O4): STUDI KOMPARASI METODE KONVENSIONAL DAN METODE SONOKIMIA - Maya Rahmayanti (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2020)
Magnetite (Fe3O4) is one of the iron oxide compounds which has strong magnetic properties so that it is widely modified with other materials for application in solid phase extraction. This study aims to compare the physical and chemical properties of magnetite synthesized by conventional methods and magnetite synthesized by sonochemical methods. The physical and chemical properties of magnetite were studied using Fourier Transform Infrared (FTIR) and X-Ray Difraction spectrophotometry. Magnetite saturation magnetization (Ms) was measured using a Vibrating Sample Magnetometer (VSM). The results of FTIR characterization showed that the absorption at a wave number of 780 cm-1 was a typical absorption of magnetite Fe-O bonds both on magnetite synthesized through sonochemical and conventional methods. The difference in crystallinity of magnetite synthesized by the two methods was not significant. The Ms magnetite value synthesized by sonochemical method was higher than the Ms magnetite value synthesized by conventional method. Keywords: magnetite, Fe3O4, synthesis, conventional, sonochemical